Enhancing B1 EFL learners’ reading comprehension through text structure awareness - Moydinova, Elmira Kamariddinovna; Jo‘rabekova, Nigora Bahodirovna (The Lingua Spectrum, 2026)
Reading comprehension is considered to be an important part of foreign language proficiency and scholastic achievement. At the same time, it is often observed that EFL school students face difficulties in extracting the meaning of written texts. This article is about the effect of teaching text structure awareness on the reading comprehension of B1 level EFL students in Uzbekistan. This is a quasi-experiment in which the researcher randomly assigned thirty students from different secondary schools in Uzbekistan into two groups. One group of students received systematic training in reading comprehension through text structure awareness strategies, whereas the other group of students received traditional reading instruction. The researcher used the standardized B1 level reading comprehension test to assess the reading comprehension of the students in the experimental and control groups. The reliability of the test was also calculated in JASP software (Cronbach’s α = .84). The results showed no significant difference in the reading comprehension of the students in the experimental and control groups before the intervention. At the same time, the results showed significant improvement in the reading comprehension of the students in the experimental group after receiving systematic training in reading comprehension through text structure awareness strategies.